N-heterocyclic silylenes as powerful steering ligands in catalysis - Raoufmoghaddam, Saeed; Zhou, Yu-Peng; Wang, Yuwen; Driess, Matthias (Journal of organometallic chemistry, 2017)
The present review highlights the role of N-heterocyclic silylene (NHSi) ligands, the silicon analogues of N-heterocyclic carbenes (NHCs), utilized in various catalytic organic transformations. The application of such novel ligands coordinated by different metal sites offers massive opportunities in organic synthesis. Despite significant advances in the synthesis of NHSi-based metal complexes, the use of these compounds in organic methodologies is still in its initial stages. Since NHSi ligands promote the σ donor-ability of phosphines and even that of NHCs, they can facilitate catalytic events by lowering the energy barrier of the rate limiting steps such as oxidative additions. This encourages scientists to utilize NHSi-metal complexes in exploiting catalyzed reactions and to revisit and improve various existing organic methodologies. This is demonstrated in several showcases of organic transformations including the Heck coupling, Suzuki coupling, alkyne and ketone hydrosilylation, amide reduction, cyclotrimerization of alkynes (in the absence and the presence of an organo cyanide), and Sonogashira cross-coupling reactions. The latter represents a novel and unexpected steering function of NHSi-based systems in homogeneous catalysis. [Display omitted] •Synthesis and catalytic performance of monodentate, bidentate, and tridentate NHSi-transition metal complexes.•Stronger σ donor strength of NHSi ligands in comparison to NHCs and phosphines.•Catalytic performances of transition metal NHSi complexes.